The Beneficial Effects of Abdominal Massage on Constipation and Quality of Life: A Literatur Review - Hasmi Hasmi; Agung Waluyo; Usman Barus Ohorella (Indonesian Contemporary Nursing Journal, 2020)
Introduction: The prevalence of constipation has increased significantly as a person ages causing an increase in the incidence of constipation in the elderly can reach 50% and can increase to 74% in patients who are in nursing home. There are a variety of standard interventions used to overcome constipation problems including diet, fluid and physical activity modification. Nursing interventions used to treat constipation are abdominal massage (abdominal massase). The purpose of this review literature is to explain the effectiveness of abdominal massase on constipation and quality of life. Method: The method used to compile the literature review is by searching through an electronic database. Searching for articles is done by using the keywords abdominal massase, constipation, randomized controlled trial, then traced through Scopus, Ebscohost, Sciencedirect, Proquest, Pubmed; 7 articles were selected from the search results, the research design was a randomized controlled trial pre-post test control and group intervention. Results: Based on the article that has been reviewed, abdominal massase intervention has a significant effectiveness in reducing the problems and symptoms of constipation experienced by elderly patients, post-orthopedic surgery patients and patients with multiple sclerosis. Conclusion: Subsequent abdominal massase interventions have also been shown to have an effect on improving the quality of life of patients with constipation.